Collaborative Tools and the Practicalities of Professional Work at the International Monetary Fund - Harper, Richard; Sellen, Abigail (Proceedings of CHI '95, Denver, CO., May 7-11, 1995)
We show how an ethnographic examination of the International Monetary Fund in Washington, D.C. has implications for the design of tools to support collaborative work. First, it reports how information that requires a high degree of professional judgement in its production is unsuited for most current groupware tools. This is contrasted with the shareability of information which can 'stand-alone'. Second, it reports how effective re-use of documents will necessarily involve paper, or 'paper-like' equivalents. Both issues emphasise the need to take into account social processes in the sharing of certain kinds of information.